Structural basis for PtdInsP2-mediated human TRPML1 regulation - Michael Fine (Nature Portfolio, 2018)
Transient receptor potential mucolipin 1 (TRPML1) is a lysosomal channel which maintains the low pH and calcium levels for lysosomal function. Here authors use structural biology and electrophysiology to show how lipids bind and allosterically activate TRPML1.